Study on Internally Displaced Population, Gender and Livelihoods in Kassala State, Eastern Suden - Saeed Ali, Awadalla Mohamed (World Bank, Washington, DC, 2014)
This study on “internally displaced population, gender and livelihoods in Kassala State, Eastern Sudan” was carried out to deepen the analytical work being conducted by the “Sustainable Livelihoods for Displaced and Vulnerable Communities in Eastern Sudan Project (SLDP)”. It was undertaken to gain a better understanding of gender and conflict issues that can serve as a direct input to support project operations and scaling up, and more urgently to provide guidelines for implementation of the piloting phase of the SLDP in a gender sensitive manner that also targets the provision of equitable livelihood support services to the internally displaced population groups and members of the vulnerable host communities in the targeted locations. From a macro view, this study feeds into the larger research project entitled “Learning on Gender and Conflict in Africa (LOGiCA)”. The study is intended to place the focus of the SLDP on the improvement of livelihoods and services in IDP camps and host communities in rural areas by employing a gender balanced approach.